Contribution of Sectoral Credit on the Economic Growth of Nepal - Shrestha, Suprit; Maharjan, Milan; K.C., Subin (SS Multidisciplinary Research Journal, 2024)
This research paper investigates the contribution of sectoral credit to the economic growth of Nepal. Utilizing a dataset covering quarterly time series data from Fiscal Year 2010/11 quarter 1 to Fiscal Year 2022/23 quarter 2, the study employs an empirical approach to examine the relationship between sectoral credit allocation and gross domestic product (GDP). The analysis focuses on three key sectors: agriculture, service, and industry. The results indicate significant findings in both the long run and short run. In the long run, agricultural sector credit exhibits a negative impact on GDP, while service sector credit shows a positive effect. However, the impact of industrial sector credit is inconclusive. In the short run, agricultural credit positively influences GDP after a certain lag, and service credit has an immediate positive impact.